Empowerment of Youth Organizations in Building Awareness of a Clean and Healthy Environment Through Waste Banks - Sasmita, Karta; Retnowati, Elais; Azizi, Muhammad Khalif; Hadiyanti, Puji; Kuswantono, Sri (Universitas Negeri Semarang, 2022)
Garbage is a big problem nowadays, youth organizations and innovation. A waste bank is a good combination if it has collaborated. This study aims to build public environmental awareness using a walking waste bank. This study uses a qualitative approach by applying the Participation Action Research (PAR) method. This research means that a result of research that has been carried out in a participatory manner is then applied into action. The results showed that, in field research in participating in youth organization socialization to the community, the mechanism for youth socialization by visiting the community could change people's attitudes to become more disciplined and willing to participate in the waste bank program to create a clean and healthy environment. Thus, the youth empowerment program to improve skills and knowledge in conducting educational outreach to the community is suitable for youth members.